A qualitative study on participants' experiences with a community-based mindful walking intervention and mobile device activity measurement - Karyn O. Jones; Snehal S. Lopes; Claire Kelly; Ralph S. Welsh; Liwei Chen; Mark Wilson; Meenu Jindal; Heidi Zinzow; Lingling Zhang; Lu Shi (Elsevier, 2021)
Background: Mindful walking (MW) interventions employ mindfulness training combined with physical activity. Wearable mobile devices have been increasingly used to measure outcomes of physical activity interventions. The purpose of this study was to understand MW participants' attitudes towards MW and the use of mobile devices in health promotion interventions, including barriers and facilitators of intervention engagement and adherence. Few qualitative studies have documented participant experience with these two types of interventions. Method: The pilot study involved a randomized MW intervention including 38 participants with self-reported inadequate physical activity. Half of them were randomized to receive MW intervention plus a FitBit device and the other received the FitBit device only. We used a qualitative thematic analysis of the narrative data collected through open-ended survey questions at three time points. Participants in the MW intervention were asked to describe their experiences with MW, while all participants were asked to describe their experience with wearing the FitBit to track their step counts. Results: Participants reported a broad range of perceived benefits and challenges related to adopting the MW intervention and using the mobile device. Participants were generally willing to try to adopt the recommended MW practice and to see value of MW in increasing physical activity and improving overall health. Participants reported using a variety of additional device features beyond goal setting and step counts, indicating using the devices may have been effective in providing additional motivation for participants in meeting physical activity goals in both the control and intervention groups. While most of the feedback about MW (in the intervention group) and the device (all participants) was overwhelmingly positive, a minority of participants reported barriers such as lack of patience with meditation and discomfort with wearing the device. Conclusion: Most participants in the MW intervention see the health benefits of this program and most participants using the wearable physical activity tracking device reported the motivational benefits of this device. Issues with the MW intervention (e.g., lack of patience) and the wearable device (e.g., discomfort with wearing) need to be addressed in future interventions.